Surface texturing for tribomechanical performance optimisation of epoxy composites reinforced with chemically activated carbon - Leonard Maduabuchi Akuwueke; Chinwuba Victor Ossia; Harold Ugochukwu Nwosu (Tribology and Materials)
The effects of surface texturing on the tribomechanical properties of epoxy composites reinforced with chemically activated carbon were studied. Activated carbon produced from palm kernel (PKSAC) and coconut shells (CSAC) were composed in three concentrations (XCSAC): 100 vol. % CSAC + 0 vol. % PKSAC, 50 vol. % CSAC + 50 vol. % PKSAC and 0 vol. % CSAC + 100 vol. % PKSAC, three particle sizes (XPS): 60, 105 and 150 μm, three reinforcement amounts (XRW): 4, 6 and 8 wt. %, and used to fabricate cylindrical discs of Ø 50 × 6 mm height with four surface texture geometries. The epoxy/activated carbon composites were experimentally evaluated for tribomechanical performance using Box-Behnken design. Multivariate second-order polynomial models approximated the influence of XCSAC, XPS and XRW on the tribomechanical properties. The aim was to use the property response to determine the effect of texturing on the tribomechanical properties of composites for automobile applications. The maximum tensile strength value was the highest for the untextured surface, followed in descending order by circular, triangular and rectangular surface texture. The maximum compressive strength value was the highest for the untextured surfaces, followed in descending order by triangular, circular and rectangular surface texture. The maximum wear rate value was the highest for the untextured surfaces, followed in descending order by rectangular, circular and triangular surface texture, while the maximum coefficient of friction value was the highest for the circular surface texture, followed in descending order by triangular and rectangular surface texture and untextured surfaces. Texturing surfaces were found to reduce the composites' mechanical properties while decreasing the wear rate and increasing the coefficient of friction.